Análisis de sistemas LOS UOWC a través de software de simulación. - Medranda Cobeña, Gema Isabel (2024)
The analysis of direct line-of-sight systems in submarine links (LOS UOWC) using Optisystem simulation software is crucial to evaluate the performance of submarine optical communications. The general and specific objectives of the research are established, addressing the fundamentals of submarine optical communications and analyzing the performance of Optisystem software for LOS-type submarine channels. The methodology employed is exploratory and descriptive, allowing a thorough understanding of the characteristics and behaviors of LOS links in underwater environments, identifying key parameters for the optimization of LOS UOWC systems. Simulation and analysis of results are essential, evaluating the performance of LOS UOWC systems through simulation software. Conclusions are presented based on the results obtained and possible recommendations for future research in this field are discussed, highlighting the importance of simulation and detailed analysis to improve the efficiency and reliability of direct line-of-sight underwater optical communications. Keywords: submarine links, submarine channels, direct line-of-sight, submarine optical communications, Optisystem